Perkiraan Angka Migrasi Neto Perkelompok Umur Provinsi Jawa Barat Tahun 2020 dan 2021 - Ilma Diana Rosa; Yayat Karyana (Jurnal Riset Statistika, 2023)
Abstract. Population dynamics in an area are influenced by factors of mortality, fertility and migration. In the study of population dynamics between regions in Indonesia, the migration factor has an important position based on a spatial and temporal approach to examine the accumulation and distribution of population in an area. Population migration is an integral part of the entire development process, as well as a cause and recipient of the impact of changes in the economic and social structure of a region. The research method to be used is a literature study or case study. Case study, namely a comparison of net migration of the population of West Java Province per age group in 2020-2021 using the Population Growth Rate (LPP) of West Java Province and Indonesia's Population Growth Rate (LPP) of 2020-2021, population of West Java Province per age group in 2020- 2021 from the results of the 2020-2021 Population Census (SP) portrait, West Java Province's Age Specific Net Migration Rate (ASNMR) in 2015. Literature study is studying basic theories related to migration. The Population Growth Rate (LPP) in West Java Province in 2020 is 1.11 percent per year, and the Population Growth Rate (LPP) in West Java Province in 2021 is 1.41 percent per year. the Covid-19 Virus outbreak and the Central Statistics Agency (BPS) find it difficult to retrieve this data. With a National Population Growth Rate of 1.25 percent per year, it is considered higher because of the difference in natural growth with the difference in the population's death rate and birth rate. Abstrak. Dinamika kependudukan di suatu daerah dipengaruhi oleh faktor-faktor mortalitas, fertilitas, dan migrasi. Kajian dinamika kependudukan antar wilayah di Indonesia, faktor migrasi penting kedudukannya berdasarkan pendekatan spasial dan temporal untuk mencermati akumulasi dan persebaran penduduk pada suatu wilayah. Migrasi penduduk merupakan bagian integral dari keseluruhan proses pembangunan, serta sebagai penyebab dan penerima dampak perubahan struktur ekonomi dan sosial suatu wilayah. metode penelitian yang akan digunakan adalah studi lietratur atau studi kasus. Studi kasus, yaitu perbandingan migrasi neto penduduk Provinsi Jawa Barat perkelompok umur tahun 2020-2021 menggunakan Laju Pertumbuhan Penduduk (LPP) Provinsi Jawa Barat dan Laju Pertumbuhan Penduduk (LPP) Indonesia tahun 2020-2021, penduduk Provinsi Jawa Barat per kelompok umur tahun 2020-2021 dari hasil potret Sensus Penduduk (SP) tahun 2020-2021, Age Specific Net Migration Rate (ASNMR) Provinsi Jawa Barat tahun 2015. Studi literatur yaitu mempelajari teori-teori dasar yang berkaitan dengan migrasi. Pada Laju Pertumbuhan Penduduk (LPP) di Provinsi Jawa Barat tahun 2020 sebesar 1,11 persen pertahun, serta pada Laju Pertumbuhan Penduduk (LPP) di Provinsi Jawa Barat tahun 2021 sebesar 1,41 persen pertahun data tersebut lebih besar dari tahun sebelumnya, dikarenakan adanya wabah Virus Covid-19 serta Badan Pusat Statistika (BPS) sulit untuk mengambil data tersebut. Dengan Laju Pertumbuhan Penduduk Nasional sebesar 1,25 persen pertahun, dianggap lebih besar karena perbedaan pertumbuhan alamiah dengan selisih penduduk angka kematian dan angka kelahiran.